2016
DOI: 10.1155/2016/7864150
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Protects Pancreatic Acinar Cell Injury by Modulating Nrf2‐Mediated Oxidative Stress and NLRP3 Inflammatory Pathway

Abstract: Acute pancreatitis (AP) is characterized by early activation of intra-acinar proteases followed by acinar cell death and inflammation. Cellular oxidative stress is a key mechanism underlying these pathological events. Sulforaphane (SFN) is a natural organosulfur antioxidant with undescribed effects on AP. Here we investigated modulatory effects of SFN on cellular oxidation and inflammation in AP. AP was induced by cerulean hyperstimulation in BALB/c mice. Treatment group received a single dose of 5 mg/kg SFN f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 54 publications
4
51
1
2
Order By: Relevance
“…AP is an acute inflammatory disease of the digestive system. Although the pathogenesis of AP still remains controversial, the oxidative stress pathway is recognized as one of the classical underlying mechanisms in the early phase of AP [19]. Under physiological conditions, oxidative stress damage could be inhibited by antioxidant defense system, consisted of nonenzymatic antioxidants to scavenge reactive oxygen species (ROS) and antioxidase to catalyze the elimination of ROS accumulation [20].…”
Section: Discussionmentioning
confidence: 99%
“…AP is an acute inflammatory disease of the digestive system. Although the pathogenesis of AP still remains controversial, the oxidative stress pathway is recognized as one of the classical underlying mechanisms in the early phase of AP [19]. Under physiological conditions, oxidative stress damage could be inhibited by antioxidant defense system, consisted of nonenzymatic antioxidants to scavenge reactive oxygen species (ROS) and antioxidase to catalyze the elimination of ROS accumulation [20].…”
Section: Discussionmentioning
confidence: 99%
“…GSK3- β has been shown to function as a negative regulator of Nrf2, a protein involved in signaling pathways that plays a critical role in the defense against oxidative and toxicological stress via upregulation of antioxidant and detoxifying enzyme expression [ 32 , 33 ]. In addition, Nrf2 activation has also been reported to protect against inflammation [ 34 ]. Nrf2 has been shown to attenuate inflammatory responses through a number of mechanisms, including the induction of the anti-inflammatory enzyme, hemeoxygenase-1(HO-1) [ 35 ], the negative regulation of proinflammatory cytokine expression [ 36 ], and chemokine expression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under the physiology condition, Nrf2 is located in the cytoplasm. When Nrf2 is activated, it is translocated into the nucleus and combined with the ARE to induce a series of cytoprotective enzymes such as HO-1 [49, 50] and NQO-1 [51, 52] to enhance the antioxidant capacity of cells and protect cells from the oxidative injury [53, 54]. In the present studies, the elevation of Nrf2, HO-1, and NQO-1 at mRNA and protein levels found in SE rats 24 hrs but not 7 days following Li-Pc injection indicated that epileptic seizures could transiently activate Nrf2-ARE pathway [55].…”
Section: Discussionmentioning
confidence: 99%